Industry familiarity and trading: Evidence from the personal portfolios of industry insiders - Ben-David, Itzhak; Birru, Justin; Rossi, Andrea (Journal of Financial Economics, 2019)
We study whether industry familiarity is an advantage in stock trading by exploring the trading patterns of industry insiders in their own personal portfolios. To do so, we identify accounts of industry insiders in a large data set provided by a retail discount broker. We find that insiders trade firms from their own industry more frequently. Furthermore, they earn abnormal returns exclusively when trading own-industry stocks, especially obscure stocks (small, low analyst coverage, high volatility). In a battery of tests, we find no evidence of the use of private information. The results are most consistent with the interpretation that industry familiarity is an advantage in stock trading.